2007
DOI: 10.1021/ef7002602
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Transformation of 1,3,5-Trimethylbenzene over a USY Zeolite Catalyst

Abstract: Catalytic transformation of 1,3,5-Trimethylbenzene (TMB) has been investigated over USY zeolite catalyst in a novel riser simulator at different operating conditions. The effect of reaction conditions on the variation of isomerization to disproportionation products ratio (I/D), distribution of trimethylbenzene (TMB) isomers, xylene/tetramethylbenzenes (X/TeMB) ratio and values of p-xylene/o-xylene (P/O) ratios are reported. Comparisons are made between the results of the 1,3,5-TMB and the earlier reported valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The catalytic transformation of 1,3,5-TMB was applied as a probing reaction for the hierarchical EU-1 zeolites, which is a complex reaction including mainly isomerization and disproportionation. 16,[18][19][20] Moreover, the products of these reactions can react with each other and with the original reactants as well. 16 The conversion of bulky molecules tends to be more diffusion controlled, because the majority of the active sites of the zeolite are within its pores.…”
Section: 35-tmb Adsorption and Catalytic Transformationmentioning
confidence: 99%
“…The catalytic transformation of 1,3,5-TMB was applied as a probing reaction for the hierarchical EU-1 zeolites, which is a complex reaction including mainly isomerization and disproportionation. 16,[18][19][20] Moreover, the products of these reactions can react with each other and with the original reactants as well. 16 The conversion of bulky molecules tends to be more diffusion controlled, because the majority of the active sites of the zeolite are within its pores.…”
Section: 35-tmb Adsorption and Catalytic Transformationmentioning
confidence: 99%
“…showed that transalkylation and disproportionation mainly occur on strong acid sites, while isomerization can take place on weak acid sites. Isomerization reactions can decrease the p ‐xylene selectivity and transform the 1,2,4‐TMB to less reactive and more bulky 1,3,5‐TMB or 1,2,3‐TMB [32–36] . Furthermore, the performance of the zeolite catalyst during the transalkylation reaction is also dependent on the reaction conditions that are used.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] However, it was found that medium-pore zeolites, like ZSM-5, have a higher selectivity towards p-xylene. [21][22][23] However, direct visual evidence of this phenomena is still missing. Previously, it has been shown that transalkylation and disproportionation mainly occur on strong acid sites, while isomerization can take place on weak acid sites.…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] Finally, it has been reported that the more bulky 1,3,5-TMB and 1,2,3-TMB, formed by the isomerization of 1,2,4-TMB, diffuse slower through medium-pore zeolite due to steric constrains and will mainly react at the surface of the zeolite. [21][22][23] However, direct visual evidence of this phenomena is still missing.…”
Section: Introductionmentioning
confidence: 99%